The rapid test to determine the urine urease activity in children with urolithiasis (Bangladesh Journal of Medical Science, 2025)
Objective To study the clinical efficiency of the newly proposed Rapid Urine Urease Activity (UA) test in detecting urease–producing bacteria responsible for the formation of kidney calculi in children with urolithiasis. Materials and Methods The prospective observational study involved 80 children: 40 with urolithiasis and 40 healthy children. The urolithiasis patients were divided into three subgroups based on their urease activity. All patients underwent the Rapid Urine UA test, standard urinalysis, standard bacteriological urine test, metabolic disorder analysis in urine, and chemical analysis of removed stones. Results Urine UA levels in healthy children were 0 [0-10] mmol/l, while in urolithiasis patients, they were 57 [50-200] mmol/l. Maximum UA levels were observed when detecting pathogens such as Klebsiella pneumoniae (340 mmol/l), Proteus mirabilis (300 mmol/l), and Pseudomonas aeruginosa (256 mmol/l). Medium UA levels (51- 100 mmol/l) were recorded in patients with WBC of 23 [20-182] per mL, uric acid crystals, and acidic pH (4). Low UA levels (21–50 mmol/l) were observed in patients with no crystals in urine, a slight increase in WBC 22 [16-24] per mL. Patients in this subgroup, compared to others, exhibited disorders like hypercalciuria (25%) and hyperoxaluria (22.5%), with calcium oxalate stones in most cases. Proteus mirabilis had UA levels ranging from 58 mmol/l up to 300 mmol/l; Pseudomonas aeruginosa from 100 mmol/l up to 256 mmol/l; E. coli from 50 mmol/l up to 94 mmol/l; Klebsiella pneumoniae from 309 mmol/l up to 340 mmol/l. Conclusion The rapid urine UA test is a clinically efficient method for identifying active urease-producing bacteria in urine, contributing to the formation of infected stones in children.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 569-578